Evaluation of serotypes 5 and 8 capsular polysaccharides in protection against Staphylococcus aureus in murine models of infection - Brian L. Cheng; Travis B. Nielsen; Paul Pantapalangkoor; Fan Zhao; Jean C. Lee; Christopher P. Montgomery; Brian Luna; Brad Spellberg; Robert S. Daum (Human Vaccines & Immunotherapeutics, 2017)
Staphylococcus aureus is the leading cause of nosocomial and community-acquired infections, including soft tissue and skin infections and bacteremia. However, efforts to develop an effective vaccine against S. aureus infections have not been successful. We evaluated serotypes 5 and 8 capsule polysaccharides (CP) CRM197 conjugates as vaccine candidates in murine models of bacteremia, lethal sepsis, and skin infection. The conjugate vaccines elicited a good antibody response, and active immunization of CP5-CRM or CP8-CRM conjugates protected against staphylococcal bacteremia. In the skin infection model, CP8-CRM but not CP5-CRM protected against dermonecrosis, and CP8-CRM immunization significantly decreased the bacterial burden in the lesion. However, neither CP5-CRM nor CP8-CRM protected against mortality in the lethal sepsis model. The results indicate the capsular vaccines elicit protection against some, but not all, aspects of staphylococcal infection.